Neoxela: A new replacement name for Xela Botero, Bezark & Santos-Silva, 2020 (Coleoptera, Cerambycidae, Lamiinae) - Botero, Juan Pablo; Bezark, Larry; Santos-Silva, Antonio (Zootaxa, 2022)
Recently, Botero, Bezark & Santos-Silva (2020) described a new genus of Methiini (Cerambycinae), Xela, for their new species Xela tysoni, from Guatemala. Currently, the genus remains monotypic and the species is known only from their type locality. Unfortunately, the authors did not realize that the name had already been used for a trilobite species (Xela drena Jell, 1990). Herein, we propose a new replacement name for the genus.